History for 11-14 years - Quinn, Rob; Evans, R. Paul (Curriculum for Wales, 2022)
Tell the story of Wales over the last 1000 years, as you discover how Welsh history, cynefin, culture and language are connected, from the past to the present. Underpinned by the four purposes of the new Curriculum for Wales, this book empowers pupils with the knowledge and skills that they need for learning, life and work. > Design a curriculum that is unique to your school. Use the content flexibly to craft a historical education that reflects your pupils and your local area, as well as covering 'What matters' statements within the Humanities AoLE. > Follow an enquiry-based approach. Starting in early medieval times, this book establishes a strong chronological spine, with later enquiries looking at changes in Wales thematically. > Develop analytical and evaluative skills. A wide range of sources and interpretations encourage pupils to think like historians, using evidence to consider change and continuity, cause and consequence. > Put progression at the heart of the curriculum. End-of-topic Activities build towards more in-depth end-of-enquiry Review and Research tasks. All activities and tasks enable each pupil to move through their individual learning journey towards their next 'Progression step'. > Explore the rich history of Wales and the global context. Understanding events and issues in Wales and the wider world - and the development of Wales as a multicultural society - will help pupils to become ethical, informed citizens.